Beyond Growth: A Provincial-Level Assessment of the Doughnut Economy’s Potential in Indonesia - Rahma, Hania; Fauzi, Akhmad (European Journal of Sustainable Development, 2024)
The focus on a growth-oriented development paradigm has led to unsustainable outcomes such as environmental degradation, resource depletion, increased inequality, and compromised social well-being. An alternative approach known as the Doughnut Economy has emerged, offering a new economic development model that aims to guide humanity towards staying within planetary boundaries. The Doughnut model visualizes sustainable development with an ecological ceiling as the outer limit and a social foundation as the inner boundary. This study attempts to create a Doughnut Economy Index for 34 provinces in Indonesia, categorizing them into four groups to assess how well they meet societal needs while remaining within planetary limits. The index, derived from a simple formula, yields two indices: social performance and ecological damage. The research reveals that only three out of the 34 provinces in Indonesia fall within the safe zone of the Doughnut model. Shortfall issues are prevalent in Eastern Indonesian provinces like Papua, Maluku, and Nusa Tenggara Islands, while overshoot concerns are more prominent in provinces in Kalimantan and Java & Bali Islands. Keywords: Growth-oriented paradigm, Doughnut Economy, sustainable development, regional development, Doughnut Economy Index